2013
DOI: 10.1186/1471-2431-13-21
|View full text |Cite
|
Sign up to set email alerts
|

In-line filtration minimizes organ dysfunction: New aspects from a prospective, randomized, controlled trial

Abstract: BackgroundInfused particles induce thrombogenesis, impair microcirculation and modulate immune response. We have previously shown in critically ill children, that particle-retentive in-line filtration reduced the overall complication rate of severe events, length of stay and duration of mechanical ventilation. We now evaluated the influence of in-line filtration on different organ function and thereby elucidated the potential underlying pathophysiological effects of particle infusion.MethodsIn this single-cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 29 publications
0
72
0
Order By: Relevance
“…Their study demonstrate potential beneficial effects of in-line filtration on the preservation of various organ systems, even if further experimental and clinical investigations are necessary to clarify the exact impact of infused particles [36].…”
Section: Drug Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their study demonstrate potential beneficial effects of in-line filtration on the preservation of various organ systems, even if further experimental and clinical investigations are necessary to clarify the exact impact of infused particles [36].…”
Section: Drug Interactionsmentioning
confidence: 99%
“…The SIRS is related to the particle administration during infusion, and has already been well demonstrated for adult patients of intensive care units [22], and more recently in the pediatric population [36].…”
Section: Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also showed that particulate contamination could be present downstream from the in-line filter, with particles greater than 10 µm. Nevertheless, the benefits of these filters have been challenged by several authors [3,67,68]. A meta-analysis did not provide specific justification for using in-line IV filters to prevent morbidity and mortality [69] and there may be a problem in clinical practices due to the ineffectiveness of the therapeutic management.…”
Section: Drug Incompatibilities: a Problem In Clinical Practicementioning
confidence: 99%
“…Recently, studies have investigated the impact of particulate contamination on organ failure in critically ill children. Boehne et al [68] evaluated the clinical impact of particulate contamination on different organs, as defined by the International Pediatric Sepsis Conference 2005 [109]. They concluded that the infusion of particles may cause alteration to the microcirculation, inducing systemic inflammatory reactions with adverse effects on organs.…”
Section: Systemic Clinical Effectsmentioning
confidence: 99%